Ethnobotany of flower trading in traditional markets of Banyumas, Central Java, Indonesia - Alfian, Rahman Latif; Harahap, Junardi; Supangkat Iskandar, Budiawati; Hyung-Jun, Kim (BRIN Publishing (Penerbit BRIN), 2025)
ALFIAN, R. L., HARAHAP, J., ISKANDAR, B. S. & HYUNG-JUN, K. 2025. Ethnobotany of flower trading in traditional markets of Banyumas, Central Java, Indonesia. Reinwardtia 24(2): 219‒236. —Flower trading has long been present in society. Particularly in Javanese society, flowers hold significant biological importance in social and cultural life. Flowers are imbued with various symbolic meanings and are used in various life events and religious rituals. This study aims to explore the existence of flower trading within the community, especially in the Banyumas region. In addition to delving into the trade itself, this research also investigates the types of flowers being traded, how they are sourced for sale, the meanings attached to these flowers, how each type of flower and plant is sold, and how the classification of flower types according to the community is divided. This study employs a qualitative ethnographic method to gather research data. The findings of this research indicate that the existence of Rampe flower traders must be distinct from the community's cultural traditions, particularly in Banyumas. Rampe flower traders typically sell several flowers used as essential components in religious and cultural ceremonies. These flowers include roses (Rosa hybrida), ylang-ylang (Cananga odorata), white magnolia (Magnolia), and several other flowers. Most Banyumas people use these flowers for the tradition of grave pilgrimage. White and yellow magnolia flowers have a higher economic value as traders sell them in seed form. Rampe flower traders classify plants into those with high economic value and those with regular value. The high economic value of a flower is usually influenced by its availability (rarity) and the specific functions of certain types of flowers. Meanwhile, plants with regular economic value are typically complementary plants (not core plants) in the community's cultural and religious traditions.